THE EFFECT OF HYPOXIC BRAIN DAMAGE ON THE SURVIVAL OF PREMATURE INFANTS - N. V. Likholetova (Scientific Сentre for Family Health and Human Reproduction Problems, 2018)
The central nervous system injuries are a common neonatal pathology, hypoxia being one of the main causes of cerebral dysfunction. The purpose of this study was studying the incidence of hypoxic cerebral disorders in premature infants with an extremely low body weight and a very low birth weight and revealing the risk factors that adversely affected the disease outcome. The subject of the study was preterm infants whose gestational age did not exceed 31 weeks. The main criterion for inclusion into the study was the presence of hypoxic-ischemic and hypoxic-hemorrhagic brain damage. To reveal the perinatal risk factors, the somatic health of mothers, and pregnancy and childbirth peculiarities were studied. The structure of children’s pathology and intensive care techniques were analyzed. Cerebral disorders were verified in 42 out of 176 patients (23.5 %). 2–3rd-degree intraventricular hemorrhage was diagnosed in 34 newborns (80.9 %), severe ischemia in 8 children (19.1 %). To determine the structure of the disease outcome, all children were divided into deceased and survivors. A fatal outcome was observed in 14 cases (33.3 %). The mothers of deceased children were more likely to have obstetric and concomitant extragenital pathologies. Analysis of pediatric pathology showed that the hemodynamically significant functioning arterial duct and severe asphyxia in childbirth were much more frequent in deceased children. Intensive therapy of deceased children included «hard» parameters of artificial ventilation and high doses of cardiotonic drugs. Thus the presented risk factors can be considered as predictors of an unfavorable outcome in children with this pathology.